Mass absorption cross-section of flare-generated black carbon: Variability, predictive model, and implications. (August 2019) - Conrad, B.M.; Johnson, M.R.
Abstract: Global gas flaring is an important source of black carbon (BC) emissions with uncertain climate impacts. The link between atmospheric concentration and direct radiative forcing (DRF) by BC is its mass absorption cross-section (MAC). MAC data for flare-generated BC are lacking in the literature and the only known data conflict with generally-accepted BC MAC values, which are assumed to be source-independent. This paper presents the first measurements of BC MAC for large-scale flares, burning globally-representative, industry-relevant flare gas compositions in a controlled facility. BC MAC was calculated with precisely-quantified uncertainties using photoacoustic and thermal-optical instruments. Flare-generated carbon was found to be primarily elemental in composition (typically >92%), and most probably externally-mixed based on detailed analysis of attenuation vs. evolved carbon data and consideration of flare-specific mechanisms for organic carbon emissions. Flare BC MAC was generally larger than well-cited literature values and had statistically significant variations with fuel and operating conditions. Variability in BC MAC was well-predicted by a novel phenomenological model based on flame radiative characteristics and relative BC production. The derived model consolidates previously-unreconciled disparate data from different sources and suggests that flare BC MAC is likely >1.3–2 times standard values, implying an underestimation of DRF by flare-generated BC. Graphical abstract: Image 1